Assessing the Impact of Foreign Direct Investment on Vietnam's Socioeconomic Development and Proposing Policy Recommendations - Thi Phuong Linh, Nguyen; Phuong Thao, Nguyen (VNU Journal of Science: Policy and Management Studies; Vol 40 No 3DO - 10.25073/2588-1116/vnupam.4486, 2024)
In recent years, Vietnam has emerged as one of the world's top 20 destinations for foreign direct investment (FDI). Since reforming its Foreign Investment Law in 1987 and joining the World Trade Organization (WTO) in 2007, the country has implemented numerous tax and investment procedure reforms. This influx of FDI has significantly boosted Vietnam's economic growth, job creation, and social welfare. However, challenges persist—complex legal procedures and weak links between FDI and domestic businesses have been ongoing issues for four decades. Moreover, new global economic trends such as the global minimum tax, sustainable development, digital transformation, and the shift towards a circular economy demand timely and appropriate government reforms. These reforms are crucial for developing suitable foreign investment policies and effective FDI attraction strategies. This article aims to examine Vietnam's current FDI landscape, assess its socio-economic impact in recent years, and propose recommendations for a more selective and effective FDI strategy moving forward.